Un análisis del ordenamiento y alomorfía en la flexión verbal del quechua ayacuchano desde la morfología distribuida - Martel Paredes, Víctor Arturo (Pontificia Universidad Católica del Perú, 2022)
This article presents a new approach to the (re)ordering of SUBJECT and OBJECT morphemes in verb agreement of Ayacuchan Quechua. Our analysis is based on Distributed Morphology (Halle and Marantz 1993), which proposes operations on morphemes in the morphological component. We conclude that the addressee feature of the second-person OBJECT morpheme –nki «wins» when it comes to specificity and, therefore, it appears in a SUBJECT position, which results in the occurrence of –yki as an allomorph and the appearance of –su. Finally, we propose the occurrence of –su as a transitional defective morpheme, which cannot be considered as a third or second person pronoun.

Este trabajo presenta una nueva propuesta al (re)ordenamiento de morfemas de SUJETO y de OBJETO en la concordancia verbal del quechua ayacuchano. El análisis se basa en la morfología distribuida (Halle y Marantz 1993), que propone operaciones sobre morfemas en el componente morfológico. Se concluye que el rasgo OYENTE del morfema de OBJETO de segunda persona -nki gana en especificidad y, por tanto, se realiza en posición de SUJETO, con el costo de la aparición de –yki como alomorfía y la aparición de –su. Finalmente, proponemos que –su es un morfema transicional defectivo con rasgo OYENTE, que no puede ser interpretado como pronominal de tercera ni de segunda persona.
An Analysis of the Ordering and Allomorphy of Verbal Inflection in Ayacuchan Quechua from the Distributed Morphology Approach
Keywords: Distributed Morphology; Quechua; Ordering; Person; Allomorphy; Morfología distribuida; Quechua; Ordenamiento; Persona; Alomorfía; https://purl.org/pe-repo/ocde/ford#6.02.06